A new approach to examine non-linear and mediated growth and convergence outcomes of cohesion policy - Mindaugas Butkus; Alma Maciulyte-Sniukiene; Renata Macaitiene; Kristina Matuzeviciute (Economies, 2021)
This paper contributes to a wide range of studies on Cohesion policy (CP) outcomes by proposing a new approach to directly examine its effect on convergence. We extended the non-linear specification of the conditional Ø-convergence model by introducing 2- and 3-way multiplicative terms and institutions as moderators not only for growth but also for convergence. By developing and calculating conditional slope coefficients and their standard errors, we found empirical evidence that institutional quality can scale down the diminishing marginal impact of funding and even trigger its increase. Our evidence regarding changes to disaggregation levels, programming period, and CP outcomes is robust. Our research findings suggest a redistribution of funds over the 2021-2027 period in favour of projects dedicated to enhancing institutional quality.
Keywords: 330; Ø-convergence model; multiplicative term; conditional slope coefficient; conditional standard error; non-linear model